Liraglutide Ameliorates β-Amyloid Deposits and Secondary Damage in the Ipsilateral Thalamus and Sensory Deficits After Focal Cerebral Infarction in Rats - Zhu, Hui-Li; Liu, Zhang-Pei; Yang, Wan-Yong; Dong, Da-Wei; Zhao, Ying; Yang, Bing; Huang, Li-An; Zhang, Yu-Sheng; Xu, An-Ding (Frontiers in Neuroscience, 2018)
Focal cerebral infarction causes β-amyloid (Aβ) deposition and secondary neuronal degeneration in the ipsilateral thalamus. Thalamus is the subcortical center of sensory, the damage of thalamus could cause sensory deficits. The present study aimed to investigate the protective effects of liraglutide, a long-acting glucagon-like peptide-1 (GLP)-1 receptor agonist, on Aβ deposits and secondary damage in the ipsilateral thalamus after focal cerebral infarction. In addition, this study was conducted to investigate whether liraglutide could improve sensory function after focal cerebral infarction. Forty-two male Sprague–Dawley rats were subjected to distal middle cerebral artery occlusion (MCAO) and then randomly divided into liraglutide and vehicle groups, and 14 sham-operated rats as control. At 1 hour after MCAO, rats in the liraglutide and vehicle groups were subcutaneously injected with liraglutide (100 µg/kg/d) and isopyknic vehicle, respectively, once a day for 7 days. Sensory function and secondary thalamic damage were assessed using adhesive-removal test and Nissl staining and immunostaining, respectively, at 7 days after MCAO. Terminal deoxynucleotidyl transferase 2′-deoxyuridine 5′-triphosphate nick end labeling and Western blot were used to detect neuronal apoptosis. The results showed that liraglutide improved sensory deficit compared to the controls. Liraglutide treatment significantly reduced Aβ deposition compared with the vehicle treatment. Liraglutide treatment decreased the neuronal loss, astroglial and microglial activation, and apoptosis compared with the vehicle treatment. Liraglutide significantly down-regulated the expression of Bcl-2 and up-regulated that of Bax in the ipsilateral thalamus compared with the vehicle group. These results suggest that liraglutide ameliorates the deposition of Aβ and secondary damage in the ipsilateral thalamus, potentially contributing to improve sensory deficit after focal cerebral infarction.